2017
DOI: 10.19173/irrodl.v18i7.2754
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Savings from Open Educational Resources on Student Academic Goals

Abstract: Our study found that most students considered OER to be as good or better in terms of quality and engagement as traditional texts, while also allowing them to put saved funds toward their educational pursuits.  As rising costs in higher education affect current and potential students, faculty and students are looking for ways to cut costs where possible.  Open educational resources (OER) are a viable option to replace expensive traditional textbooks without sacrificing quality.  This article presents the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 12 publications
1
42
0
1
Order By: Relevance
“…Similarly, Ikahihifo, Spring, Rosecrans and Watson (2017) observed stress levels related to costs and noted opposite reactions from students enrolled in courses that used free OER in lieu of costbearing commercial resources.…”
Section: Student Consequences Related To Costmentioning
confidence: 94%
“…Similarly, Ikahihifo, Spring, Rosecrans and Watson (2017) observed stress levels related to costs and noted opposite reactions from students enrolled in courses that used free OER in lieu of costbearing commercial resources.…”
Section: Student Consequences Related To Costmentioning
confidence: 94%
“…Though "engagement" was not identified as a focus of study, several researchers have mentioned that students reported an increase in satisfaction with learning and engagement in courses when using OER (Rowell, 2015;Cooney, 2017). Only one other study specifically focused on levels of engagement when students used OER, though the domains within the construct were not clearly defined, and there seemed to be overlap in definition with "perceptions" and "use" (Ikahihifo et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Across all areas of the framework, community colleges have largely been the focus (e.g. Bliss et al, 2013;Hilton & Laman, 2012;Hilton, Gaudet, Clark, Robinson & Wiley, 2013;Hilton et al, 2014;Ikahihifo et al, 2017;Rowell, 2015;Wiley, Williams, DeMarte & Hilton, 2016). What findings may emerge from applying the COUP framework to analyzing student behaviors at private non-profit colleges?…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Notably, the opposite has also shown to be true Ikahihifo et al (2017). found that students enrolled in courses employing free OER instead of cost-bearing materials chose to reinvest their savings in other academic purchases including enrolling in and paying for additional courses.…”
mentioning
confidence: 99%